Penanaman 1000 Pohon Cemara Laut Untuk Mitigasi Abrasi di Pantai Larangan Tegal - Harira Irawan, Bei; Agus Prasetyono; Alip Toto Handoko; Fahmi Firmansyah; Mei Rani Amalia; Caesar Alwansyah Setiyanto; Fahzami Ahmad; Lulu Sabrina; Tika Widianti; Octania Meyrawati Alsaifira; Juli Riyanto Tri Wijaya (BADAN PENERBIT STIEPARI PRESS, 2024)
Larangan Tegal Beach is located in the northern part of Central Java and is a tourist destination among other beaches such as Pulau Kodok beach, Komodo beach, and others. On the way to the beach, visitors will see ponds and mangrove trees lining the edge of the road. However, unfortunately, this beach is experiencing soil erosion which is quite worrying. Every time the sea water rises, the environment around the beach, especially the stalls that serve as resting places for tourists along the beach, will be submerged. The impact of coastal erosion is not only limited to inundation of sea water, but also has negative consequences for the environment and local communities. To overcome this abrasion problem, an activity was carried out to plant 1000 sea pine trees around the coast, especially in the areas of Kedungkelor Village, Munjungagung Village, and Bojongsana Village where the procurement of sea pine tree seeds came from the Tegal Regency National and Political Unity Agency (Kesbangpol) in collaboration with the Pancasakti Tegal University Campus and the Bhakti Negara Islamic Institute for the planting process. Through this activity, it is hoped that it can reduce the impact of land erosion on the coast and provide natural protection for coastal areas from strong winds and sea waves. It is hoped that this effort can protect the coast from damage that may arise due to storms and extreme weather